Servicescape and Service Quality for E-WOM Through Memorable Experiences: A Case Of Suriwathi Hotel Restaurant - I Made Andika Pramudya Utama Winada; I Ketut Surata; Ni Wayan Giri Adnyani (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study examines the influence of service quality and servicescape on electronic word of mouth (E-WOM) through memorable customer experience at Suriwathi Hotels and Villas Legian restaurant. Using a quantitative approach with SEM-PLS, the sample consisted of 230 tourist respondents. The findings show that service quality and servicescape significantly affect memorable customer experience and E-WOM, both directly and indirectly. Memorable customer experience plays a mediating role, confirmed by the Sobel Test, while CFA results validate the construct’s reliability. The study highlights the role of memory clarity and long-term recall in shaping positive digital communication. Theoretically, it strengthens SOR theory in hospitality, and practically, it offers strategic insights for optimizing service quality and servicescape to enhance E-WOM as a promotional tool in Suriwathi Hotel Restaurant.